Instrumentation and visualization of a small-scale downdraft gasifier - Rosa, Miguel (2022)
Biomass gasification is a promising technology in the conversion of biomass into electricity, being considered the most efficient thermochemical process for such endeavor. However, some technical aspects remain unsolved and currently slow down its progress, such as the formation of tars in the gas stream. Accurate measurements of a gasifier's operational parameters are central to improve the process' performance and enhance its understanding. It is with this premise that an instrumentation and monitoring system for small scale downdraft gasifier is proposed. The instrumentation system will consist of the measurements of temperature, mass of products inside the gasifier, pressure and air flow, along with actuation of the latter. A chipKIT Max32 microcontroller board serves as the core of the proposed system and act as a link to a computer where the visualization of the process is displayed. A software application was developed in order to concurrently display all the parameters either during operation or using previously acquired data.